Way to wellness and quality of life - Neuwirth, Richard (Acta Salus Vitae, 2017)
The paper presents a description of the structure of wellness services according to its two features. It is a description of groups of activities suitable for the realization of human goals. Stages of the process of change from consideration and initial search to achievement of goal and maintaining a higher quality of life are described. In addition, there are different groups of activities: sport with the main goal of achieving adherence to sport, self-care and relaxation activities with the aim of their regular inclusion into daily life, obtaining and internal acceptance of healthy diet. There is also the goal, resilience and sense of personal freedom. The description of the spiritual path is then completed by a goal that includes the acquisition of personal potential and the ability to successfully play roles in society. The poster was inspired by lectures of Prof. Peter Rehor, Ph.D. (School of Human Kinetics and Graduate School, University of Victoria, BC, Canada), held in the College of PE and Sports, PALESTRA and by Professor PaedDr. Milada Krejci, PhD.